Perceptions of dental health professionals (DHPs) on job satisfaction in Fiji: a qualitative study - Samantha Kumar; Masoud Mohammadnezhad (BMC, 2022)
Abstract Background: Reviewing job satisfaction is crucial as it has an impact on a person's physical and mental wellbeing, as well as leading to a better organizational commitment of employees that enhances the organizations succession and progress as well as better staff retention. This study aimed to explore the perceptions of job satisfaction amongst Dental Health Professionals (DHPs) in Fiji and associated factors. Methods: This study used a phenomenological qualitative method approach commencing from August to November, 2021. The target group for this study were the DHPs who provide prosthetic services. This study was conducted among DHPs from 4 purposively selected clinics in Fiji. A semi- structured open-ended questionnaire was used to collect data. Thematic analysis was used to transcribe and analyze the audio qualitative data collected from the interviews. Results: Twenty-nine DHPs took part in the in-depth interview and the responses were grouped into three themes. The findings from the study indicate that DHPs are most satisfied with their teamwork and the relationship they have with their colleagues and co-workers, followed by the nature of the work and the supervision they received. The participants indicated that they were less satisfied with professional development opportunities and least satisfied with their pay and organizational support they receive. Conclusion: The results of this study have identified gaps and areas for improvement of job satisfaction for DHPs who provide prosthetic services in Fiji such as need for more career and professional development pathways, improved infrastructure to support prosthetic service delivery in Fiji and improve remuneration for DHPs. Understanding the factors that affect satisfaction levels and being able to act accordingly are likely to lead to positive outcomes both for DHPs and their organization.